IoT-Based Door Security System as A Countermeasure and Theft Prevention - Raditya Koesyan Dipo Pramukti; Afu Ichsan Pradana; Rudi Susanto (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2024)
A security system is very necessary when creating a system. One of them is a door lock system. There are several security systems that can be used when creating an automatic door locking system, namely using alarms and application notifications. A good security system also requires how quickly the tool or system works to give signs that someone is breaking in. By applying IoT (Internet of Things) and also the ESP32 microcontroller, we can monitor an event in real-time. With IoT-based security systems, the system can continuously operate with just stable internet and electricity. The ESP32 microcontroller is also widely used in IoT projects due to its ease of operation and affordable price. An alarm that is responsive can help us prevent criminal activities. An alarm functions to alert us of something or a situation. By combining the concepts of the ESP32 microcontroller and alarm notifications in the form of messages on Telegram, we can create a reliable system. This becomes an effective solution for securing properties and the safety of its occupants.